Cell surface membrane lysosome-associated membrane glycoprotein 2 promotes cell adhesion via abundant N-glycans in choriocarcinoma. (January 2022) - Nishino, Kimihiro; Nishiko, Yuki; Shibata, Mayu; Oda, Yukari; Watanabe, Eri; Niimi, Kaoru; Yamamoto, Eiko; Kajiyama, Hiroaki
Abstract: Introduction: Lysosome-associated membrane glycoprotein 2 (LAMP-2) is a target protein for glycosylation by N -acetylglucosaminyltransferase IV (GnT-IV), which catalyzes the formation of β1, 4GlcNAc branches on the mannose core of N -glycans in choriocarcinoma cells. However, the role of LAMP-2, especially when it is expressed in the cell surface membrane of choriocarcinoma cells, has not been well investigated in the progression of choriocarcinoma. This study aimed to elucidate the function of the cell surface membrane LAMP-2 in the malignancy of choriocarcinoma. Methods: We evaluated the localization of LAMP-2 in some choriocarcinoma cell lines and clinical samples of choriocarcinoma, normal placenta, hydatidiform mole, and invasive mole by flow cytometry, immunocytochemistry, and immunohistochemistry. We performed functional experiments using the knockout or overexpression model of LAMP-2 in the presence or absence of galectins. Results: LAMP-2 was observed in the cell surface membrane of some choriocarcinoma cell lines and tumor cells of choriocarcinoma tissue and trophoblasts of the placenta, hydatidiform mole, and invasive mole. Cell surface membrane LAMP-2 knockout decreased cell adhesion and invasion in choriocarcinoma cells. Conversely, cell surface membrane LAMP-2A overexpression increased cell adhesion and invasion. Experiments in the presence of galectins revealed that abundant N -glycans bound to the peptide core of the luminal side of the cell surface membrane LAMP-2 mediated cell adhesion of choriocarcinoma cells by interacting with galectins in the extracellular matrix (ECM). Discussion: Cell surface membrane LAMP-2, which is glycosylated by GnT-IV, contributes to the malignancy of choriocarcinoma by promoting cell adhesion with the ECM via abundant N -glycans. Highlights: LAMP-2 presents in the cell surface membrane of tumor cells of choriocarcinoma tissue. The cell surface membrane LAMP-2 knockout decreased cell adhesion and invasion. LAMP-2a overexpression increased cell adhesion and invasion. The cell surface membrane LAMP-2 mediates choriocarcinoma cell adhesion via abundant N -glycans.